South African Value-Added Tax: Place of supply rules for cross border supplies of services – a comparative analysis with Chapter 3 of the OECD’s International VAT/GST Guidelines - Zulch, Hendriette (Stellenbosch : Stellenbosch University, 2017)
Thesis (MAcc)--Stellenbosch University, 2017.